2019
DOI: 10.3390/f10111003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Understory Communities in Boreal Forests: Influences of Forest Type, Latitude, and Spatial Scale

Abstract: Understory vegetation hosts high biodiversity and plays a critical role in the ecosystem processes of boreal forests. However, the drivers of understory plant diversity in this high-latitude ecosystem remain uncertain. To investigate the influences of forest type and latitude on understory beta diversity at different scales, we quantified the species composition of Vaccinium uliginosum Linnaeus communities under broadleaf and coniferous forests at two latitudes at the quadrat (2 × 2 m) and plot (10 × 10 m) sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…The progression from S3 to S5 is associated with increased competition and mortality, which can reduce both R and N (Li et al, 2019). Other factors, such as stand origin, floral and faunal communities, geography and climate, and disturbance may also influence the pattern and quantitative relationships of R and N among life stages (D'Amato et al, 2009;Ostertag et al, 2014;Jin et al, 2019;Ray et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progression from S3 to S5 is associated with increased competition and mortality, which can reduce both R and N (Li et al, 2019). Other factors, such as stand origin, floral and faunal communities, geography and climate, and disturbance may also influence the pattern and quantitative relationships of R and N among life stages (D'Amato et al, 2009;Ostertag et al, 2014;Jin et al, 2019;Ray et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Species diversity is closely related to the spatial scale of measurement, both within regions (e.g., climatic zones) and between them (Stein et al, 2014;Chisholm et al, 2018;Shankar, 2019). The relationships between R, abundance (N), and spatial scale have been well discussed, with much consideration of sampling methods, including quadrat shape and size (He et al, 1996;Turner & Tjørve, 2005;Hwang & He, 2011;Jin et al, 2019). Many studies have employed nested quadrats and assessed differences in R and N by grain size (He et al, 2002;Wang et al, 2007;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, forested boreal wetlands are generally recognized as long‐term terrestrial carbon sinks (Gutenberg et al, 2019; Mu et al, 2013). Furthermore, as the largest terrestrial biomes covering 11% of the Earth's terrestrial surfaces, hemiboreal forest is also extensively found in Northeast China (Jin et al, 2019). Boreal forests and wetlands are sensitive and vulnerable to anthropogenic activities and climate change (Li et al, 2020; Șerban et al, 2021).…”
Section: Introductionmentioning
confidence: 99%